1971
DOI: 10.1071/mf9710091
|View full text |Cite
|
Sign up to set email alerts
|

The biology of a landlocked form of the normally catadromous salmoniform fish Galaxias maculatus (Jenyns). I. Life cycle and origin

Abstract: In contrast to most other members of the family Galaxiidae which live and reproduce in fresh water, Galaxias maculatus, the common jollytail of Australia and "whitebait" of New Zealand, is normaIly catadromous throughout its range (south-eastern Australia, New Zealand, and southern South America). In some athalassic inland lakes on the volcanic plains of south-western Victoria, however, a number of populations apparently descended from this species have becomelandlocked. The life cycle of the forminhabiting on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
98
1
9

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(121 citation statements)
references
References 23 publications
(30 reference statements)
13
98
1
9
Order By: Relevance
“…McDowall et al (1994) found similar durations for the first life stages when they found that G. maculatus lived at sea (free embryo and larval periods) for 103-202 days. The different adult, egg, and free embryo size of landlocked (Pollard 1971;Cussac et al 1992;Cervellini et al 1993) and diadromous populations (Benzie 1968) and probably slower larval growth rate in fresh water could be partly attributed to the scarce food resources available in oligotrophic lakes. Particularly, low food availability in the limnetic zone may be the cause of the smaller maximum metamorphic size in landlocked populations (28 mm SL), as compared with diadromous populations (>35 mm SL, McDowall et al 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…McDowall et al (1994) found similar durations for the first life stages when they found that G. maculatus lived at sea (free embryo and larval periods) for 103-202 days. The different adult, egg, and free embryo size of landlocked (Pollard 1971;Cussac et al 1992;Cervellini et al 1993) and diadromous populations (Benzie 1968) and probably slower larval growth rate in fresh water could be partly attributed to the scarce food resources available in oligotrophic lakes. Particularly, low food availability in the limnetic zone may be the cause of the smaller maximum metamorphic size in landlocked populations (28 mm SL), as compared with diadromous populations (>35 mm SL, McDowall et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Then, as they develop into juveniles, pigmentation develops rapidly, head length increases, and a pouch-like stomach develops (McDowall 1968). Larvae of landlocked G. maculatus forms are smaller than their marine counterparts (Ringuelet et al 1967;Benzie 1968;McDowall 1968McDowall , 1971Pollard 1971;Campos 1974;Cussac et al 1992;Cervellini et al 1993). In the Andes, their ontogenetic habitat shifts have only been studied in a very small, shallow lake (6 ha surface area, 3 m max.…”
Section: Introductionmentioning
confidence: 99%
“…and the two freshwater Macquaria species (2.5-4.2 mm) (Shipway 1949;Lake 1967;Llewellyn 1974;Cadwallader and Rogan 1977;Pen and Potter 1990;Harris and Rowland 1996;Neira et al 1998;Morgan and Beatty 2000;Pusey et al 2004;Trnski et al 2005 Throughout its distributional range, N. oxleyana is known to co-occur with 16 species of fishes belonging to the families Eleotridae, Melanotaeniidae, Pseudomugilidae, Galaxiidae, Ambassidae, Plotosidae, Percichthyidae, Anguillidae, and Poeciliidae (Arthington and Marshall 1993;Arthington 1996;Knight 2000, in press). Of these, the two anguillids spawn in the deep ocean (Allen et al 2002), the poeciliid Gambusia holbrooki is viviparous (live bearers) (Milton and Arthington 1983), Galaxias maculatus spawns eggs that develop out of water on moist, riparian vegetation (Pollard 1971;Allen et al 2002), and the percichthyid Macquaria novemaculeata is catadromous, breeding in estuarine areas in winter (Harris 1986;Trnski et al 2005). Eggs of N. oxleyana can be distinguished from those of the remaining sympatric species through a combination of egg shape, size and the absence of filaments (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…Se caracteriza por poseer poblaciones lacustres y diadrómicas, las primeras viven en los lagos interiores con o sin conexión con el mar y realizan su reproducción en los mismos lagos, como lo han demostrado Pollard (1971) y Campos (1979. De la población que más conocimiento biológico existe es de las estuarinas, en las que su ciclo de vida es ampliamente conocido (Figura 3), principalmente en Nueva Zelanda y Chile.…”
Section: Figura 2 Distribución Mundial Y En Chile De G Maculatusunclassified
“…El tamaño del pez es pequeño, la longitud promedio de un adulto es de 7-8cm, carece de escamas y habita aguas límnicas y estuarinas. Las poblaciones lacustres sin conexión con el mar completan su ciclo de vida en el propio lago (Pollard, 1971). Las poblaciones estuarinas, cuyo ciclo de vida es ampliamente conocido en Chile y Nueva Zelanda, los reproductores que habitan aguas limnéticas como ríos y arroyos, migran hacia el estuario donde desovan luego, la larva va al mar y regresa al río como post-larva cristalina.…”
Section: Introductionunclassified